2015
DOI: 10.1021/es5058665
|View full text |Cite
|
Sign up to set email alerts
|

Observational and Modeling Constraints on Global Anthropogenic Enrichment of Mercury

Abstract: Centuries of anthropogenic releases have resulted in a global legacy of mercury (Hg) contamination. Here we use a global model to quantify the impact of uncertainty in Hg atmospheric emissions and cycling on anthropogenic enrichment and discuss implications for future Hg levels. The plausibility of sensitivity simulations is evaluated against multiple independent lines of observation, including natural archives and direct measurements of present-day environmental Hg concentrations. It has been previously repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
238
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(252 citation statements)
references
References 123 publications
12
238
1
1
Order By: Relevance
“…Unfortunately, the natural and legacy Hg emissions inputs to models currently demonstrate factor of five differences [34]. Sensitivity simulations conducted by Amos et al [63] of historical atmospheric emissions and model rate coefficients on present-day reservoirs have shown that the largest uncertainties in quantifying the legacy contribution arise from parameterizations of air-sea exchange, retention of Hg in soil, and disturbance of coastal sediments.…”
Section: Biogeochemical Cyclementioning
confidence: 99%
“…Unfortunately, the natural and legacy Hg emissions inputs to models currently demonstrate factor of five differences [34]. Sensitivity simulations conducted by Amos et al [63] of historical atmospheric emissions and model rate coefficients on present-day reservoirs have shown that the largest uncertainties in quantifying the legacy contribution arise from parameterizations of air-sea exchange, retention of Hg in soil, and disturbance of coastal sediments.…”
Section: Biogeochemical Cyclementioning
confidence: 99%
“…Upon deposition, mercury can be re-emitted to the atmosphere or converted -in aquatic systems -to methylmercury (Driscoll et al, 2013). Anthropogenic activities have altered the global geochemical cycle of mercury, enhancing the amount of mercury circulating in the atmosphere and surface oceans by at least a factor of 3 (Lamborg et al, 2014;Amos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, mercury oxidation processes have been the focus of the international mercury community in recent years Cohen et al, 2016;Amos et al, 2015;Dastoor et al, 2015;Song et al, 2015;Bieser et al, 2014a;De Simone et al, 2014;Qureshi et al, 2011;Travnikov et al, 2010).…”
Section: Introductionmentioning
confidence: 99%